Generation of a novel mouse model of nemaline myopathy due to recurrent NEB exon 55 deletion - Zachary Coulson; Justin Kolb; Nesrin Sabha; Esmat Karimi; Zaynab Hourani; Coen Ottenheijm; Henk Granzier; James J. Dowling (Skeletal Muscle)
Abstract Biallelic pathogenic variants in the nebulin (NEB) gene lead to the congenital muscle disease nemaline myopathy. In-frame deletion of exon 55 (ΔExon55) is the most common disease-causing variant in NEB. Previously, a mouse model of Neb ΔExon55 was developed; however, it presented an uncharacteristically severe phenotype with a near complete reduction in Neb transcript expression that is not observed in NEB exon 55 patients. We identified by RNA sequencing that the cause of this unexpectedly severe presentation in mice is the generation of a pseudoexon containing two premature termination codons (and promoting nonsense mediated decay) at the Neb exon 55 deletion site. To prove that this is the cause of the loss of Neb transcript, and to generate a more faithful model of the human disease, we used CRISPR gene editing to remove the pseudoexon sequence and replace it with human intron 54 sequence containing a validated cas9 gRNA protospacer. The resulting “hmz” mice have a significant reduction in pseudoexon formation (93.6% reduction), and a re-introduction of stable Neb transcript expression. This new model has the characteristic features of nemaline myopathy at the physiological, histological, and molecular levels. Importantly, unlike the existing exon 55 deletion mice (which die by age 7 days), it survives beyond the first months and exhibits obvious signs of neuromuscular dysfunction. It thus provides a new, robust model for studying pathomechanisms and developing therapies for NEB related nemaline myopathy.